THE DETERMINANTS OF VOLUNTARY DISCLOSURE IN INDONESIA: A LITERATURE STUDY - Syamsudin; Khairul Saleh L. Tobing; Ria; Kumba Digdowiseiso (CV. Radja Publika, 2023)
This study focuses on the exploration of voluntary disclosure, which refers to the practice of companies willingly sharing financial information with stakeholders. Scholars conducted a comprehensive analysis of existing literature to identify the main factors that affect this voluntary sharing of information. Four crucial factors have been identified as major catalysts for voluntary disclosure. Firstly, the size of a company is a significant factor, as larger companies are more likely to engage in extensive disclosure due to their ample resources and the need for transparency, particularly in complex business operations. Secondly, the importance of profitability cannot be overstated, as companies that are profitable are more likely to reveal information in order to enhance their reputation and build trust with investors and creditors. Thirdly, the degree of leverage, which indicates the extent to which a company relies on borrowed funds, can discourage the voluntary release of information. This is because high leverage increases financial risk, leading to a more cautious attitude towards disclosure. Lastly, the ownership structure has the ability to influence the disclosure practices. Companies that have family ownership or majority shareholders who prioritize privacy typically tend to refrain from engaging in extensive voluntary disclosure. Gaining insight into these factors is crucial, as they provide clarity on the reasons behind companies' disclosure strategies, addressing the requirements and anticipations of different stakeholders while managing the intricacies of financial openness.